2021
DOI: 10.1186/s12915-021-01064-7
|View full text |Cite
|
Sign up to set email alerts
|

Do all mice smell the same? Chemosensory cues from inbred and wild mouse strains elicit stereotypic sensory representations in the accessory olfactory bulb

Abstract: Background For many animals, chemosensory cues are vital for social and defensive interactions and are primarily detected and processed by the vomeronasal system (VNS). These cues are often inherently associated with ethological meaning, leading to stereotyped behaviors. Thus, one would expect consistent representation of these stimuli across different individuals. However, individuals may express different arrays of vomeronasal sensory receptors and may vary in the pattern of connections betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 92 publications
9
34
0
Order By: Relevance
“…Examples of typical MUP ligands (VOCs) previously studied in mice (Cavaggioni et al, 1987;Novotny et al, 1999;Zidek et al, 1999;Sharrow et al, 2003;Bingham et al, 2004) are presented in Figure 1B. For their complexity (volatiles, non-volatile proteins, and peptides), body secretions are now seen as signature mixtures rather than pheromones (Brennan and Kendrick, 2006;Nagel et al, 2018;Roberts et al, 2018;Bansal et al, 2021).…”
Section: Chemical Communicationmentioning
confidence: 99%
See 3 more Smart Citations
“…Examples of typical MUP ligands (VOCs) previously studied in mice (Cavaggioni et al, 1987;Novotny et al, 1999;Zidek et al, 1999;Sharrow et al, 2003;Bingham et al, 2004) are presented in Figure 1B. For their complexity (volatiles, non-volatile proteins, and peptides), body secretions are now seen as signature mixtures rather than pheromones (Brennan and Kendrick, 2006;Nagel et al, 2018;Roberts et al, 2018;Bansal et al, 2021).…”
Section: Chemical Communicationmentioning
confidence: 99%
“…These signals are often complex and provide information about multiple states of an individual including (sub-)species, kin, sex, health, and food sources ( Hurst et al, 1997 , 1998 ; Zala et al, 2004 , 2015 ; Cheetham et al, 2007 ; Stopková et al, 2007 ; Bímová et al, 2009 ). Different types of molecules manifest the complexity of such signals which are detected via chemosensory G-protein coupled receptors of the main olfactory epithelia (MOE) and of the vomeronasal organ (VNO; Moss et al, 1997 ; Leinders-Zufall et al, 2000 ; Spehr et al, 2006 ; Wynn et al, 2012 ; Ibarra-Soria et al, 2014a ; Nagel et al, 2018 ; Santoro and Jakob, 2018 ; Van Der Linden et al, 2018 ; Miller et al, 2020 ; Bansal et al, 2021 ). These receptors are tuned to particular signalling molecules including the volatile organic compounds – VOCs ( Berghard and Buck, 1996 ; Malnic et al, 1999 ; Kwak et al, 2012 , 2013 ), short peptides ( Leinders-Zufall et al, 2004 ; Sturm et al, 2013 ) and non-volatile lipocalins, in mice, dominated by the male-biased MUPs ( Chamero et al, 2007 ; Roberts et al, 2012 ).…”
Section: Chemical Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…In accord with the role of MeA, and aromatase neurons, in sexually dimorphic social behaviors, the MeA displays structural, molecular, and functional sex differences ( Nishizuka and Arai, 1981 ; De Vries et al, 1984 ; Cooke et al, 1999 ; Morris et al, 2008a ; Bergan et al, 2014 ; Billing et al, 2020 ). In fact, the domestication process of creating isogenic mouse strains may have accentuated sex differences in circuit function ( Chalfin et al, 2014 ; Bansal et al, 2021 ). We found that the broad pattern of regional inputs to aromatase-expressing MeA neurons was conserved across males and females; however, a number of regions displayed a quantitative difference in the percentage of inputs observed in males compared with females.…”
Section: Discussionmentioning
confidence: 99%